Surface acoustic wave longitudinally coupled resonators and waveguide coupled resonators - Xu, Yufeng (My University, 1994)
Surface acoustic wave (SAW) resonators, longitudinally coupled resonators and waveguide coupled resonators are studied in this thesis. The operation principles of these devices are examined. Standing wave pattern analyses are used in explaining the operation of the longitudinally coupled resonators. The coupling-of-modes (COM) theory is extensively used to characterize these devices. The COM theory is extended to the analysis of the coupled gratings and coupled transducers in which multi-track coupling is involved. The reflection, transduction and attenuation for the gratings and transducers are described in the COM model for these elements. Closed-form solutions of the COM equations for uniform structures are obtained. The matrix expression for these solutions, because of its modular nature, makes it very easy to cascade the different elements in a device and to analyze devices with different structures. The admittance matrix and scattering matrix can be calculated over the frequency range of interest. Efficient and accurate models are developed for these devices. There is good agreement between the simulated results and the experimental ones. The design procedure and optimization of waveguide coupled resonators are discussed and demonstrated. The longitudinal field distribution of the waveguide coupled resonator is calculated at the resonant frequencies of the devices. It is demonstrated that the extended COM theory can be used in the analysis of waveguide coupled resonators with more than two tracks. A four-track waveguide coupled resonator is analyzed using the extended COM theory. Based on the understanding of the waveguide and longitudinally coupled resonators, a four-pole resonator with both longitudinal coupling and waveguide coupling is proposed and analyzed.
Keywords: Electrical and Electronics; Electrical and Electronics